Inquiry-Based E-worksheet with Local Wisdom of Brebes Central Java for High School Students’ Understanding of Reaction Rates - Elfina Salsabila; Eli Rohaeti (Universitas Pendidikan Ganesha, 2023)
Teaching materials play a significant role in facilitating effective learning, particularly when utilizing inquiry-based approaches and incorporating an appreciation of local wisdom. This research has the purpose to create an E-Worksheet based on inquiry and enriched with local wisdom from Brebes, Central Java, specifically designed for the topic of reaction rates. The research method employed is Research and Development (R&D) utilizing a 4D development model. The developed E-Worksheet encompasses six learning activities that align with the guided inquiry model, with support from the Flip PDF Professional program. The quality of the E-Worksheet is evaluated by a variety of experts, such as subject matter experts, media experts, peer reviewers, chemistry teachers, and high school students. The assessment results reveal a high degree of validity, with peer reviewers assigning a rating of 88.56% (Very Good), reviewers evaluating it as 92.05% (Very Practical), and students rating it at 91.37% (Very Good) in terms of readability. Hence, this E-Worksheet is regarded as an effective learning tool in the field of chemistry education, enabling students to actively participate in the learning process while also gaining an appreciation for indigenous knowledge.